Abusive practices in competition law - Di Porto, Fabiana, 1973-; Podszun, Rupprecht, 1976- (ASCOLA competition law, 2018)
Abusive Practices in Competition Law tackles the difficult questions presented to competition lawyers and economists regarding abusive practices: where and when is the red line crossed in competitive advances? When is a company explicitly dominant? How do you handle those who hold superior bargaining power over others but are not classed as dominant? Including analysis of the EU as well as individual nations such as the USA, Germany, France, Italy, China, Japan, Australia and developing countries, this book presents the state of the art in abusive practices in competition law research. Drawing on a variety of experiences from different jurisdictions, the authors answer the most fundamental questions concerning abusive practices, with a special focus placed on superior bargaining power, economic dependence and unconscionable conduct as thresholds for competition law interventions. Key areas such as market definition in platform markets, use of presumption in antitrust law, commitment procedures and aggregate concentration concerns are all discussed within this context. Essential reading for competition lawyers and economists, Abusive Practices in Competition Law gives comprehensive advice and insight for those dealing with antitrust concepts and practical cases of abusive conduct.